A beam steering platform enabling handheld low-cost quantum key distribution - Schreier, A; Sagar, J; Lowndes, D; Chun, H; Joshi, SK; Faulkner, G; Rarity, J; O'Brien, D (IEEE, 2024)
In this paper we present the integration of a low-cost QKD system into a low-loss, asymmetrical beam steering platform including a polarisation calibration unit. Initial results are presented demonstrating a secret key rate of 400 bit/s for the overall system.